The Contribution of Shaikh Abdurrauf As-Singkili to the Establishment of Islamic Law in the Kingdom of Aceh Darussalam in the 17th Century AD - Dzulkifli Hadi Imawan (Millah: Journal of Religious Studies, 2022)
In the 17th century AD, the Kingdom of Aceh Darussalam reached its golden peak and became an intellectual and spiritual center of Islam in the archipelago filled with many scholars. Among them was Shaykh Abdurrauf As-Singkili, who became the Qadli Malikul Adil of the Kingdom. Therefore, this study seeks to examine the contribution of Shaykh Abdurrauf as-Singkili to the grounding of Islamic law in the Kingdom of Aceh Darussalam in the 17th century AD. The research method in this study is a literature study analyzing Sheikh Abdurrauf as-Singkili’s books and related studies. The results of this study explain that Shaykh Abdurrauf As-Singkili contributed significantly to the grounding of Islamic law in the Kingdom of Aceh Darussalam when he served as the Qadli Malikul Adil, recorded the Mir’atu Thullab which was a guidebook for the qadli, and made Aceh an intellectual-spiritual center of Islam in the archipelago.